Hubungan Filsafat Ilmu Terhadap Pendidikan Dasar Di Indonesia - Maghfirah, Yumna; Angelita Sianturi, Christin; Saragi, Daulat (Journal of Practice Learning and Educational Development, 2026)
This research aims to examine the role of the philosophy of science in primary education in Indonesia, specifically the integration of epistemological, ontological, and axiological aspects into the curriculum, teaching methods, and character formation of students. The research employs a qualitative approach with a library research method thru the analysis of relevant and credible literature, including academic books, journal articles, proceedings, and educational policy documents. The research results show that epistemology strengthens students' critical thinking skills and learning independence, ontology ensures the relevance of education to social, cultural, and digital realities, and axiology emphasizes the formation of character, morality, and national identity. The implementation of the philosophy of science in curriculum policies, such as Merdeka Belajar and MBKM, demonstrates the connection between philosophical foundations and educational practices, although challenges still arise from teachers' understanding, digital literacy gaps, and globalization pressures. This research concludes that the integration of the three aspects of the philosophy of science serves as a strategic foundation for adaptive, humanistic, and relevant education in line with the times. Recommendations are given for policymakers and education practitioners to place greater emphasis on the consistent application of the philosophy of science, as well as for further research to examine its implementation in specific contexts such as digital literacy and inclusive education.